Acetylcholine modulates K+ and Na+ currents in human basal forebrain cholinergic neuroblasts through an autocrine/paracrine mechanism. Issue 4 (27th October 2020) - Coppi, Elisabetta; Cherchi, Federica; Sarchielli, Erica; Fusco, Irene; Guarnieri, Giulia; Gallina, Pasquale; Corradetti, Renato; Pedata, Felicita; Vannelli, Gabriella B.; Pugliese, Anna Maria; Morelli, Annamaria
Abstract: The Nucleus Basalis of Meynert (NBM) is the main source of cholinergic neurons in the basal forebrain to be crucially involved in cognitive functions and whose degeneration correlates with cognitive decline in major degenerative pathologies as Alzheimer's and Parkinson's diseases. However, knowledge concerning NBM neurons derived from human brain is very limited to date. We recently characterized a primary culture of proliferating neuroblasts isolated from the human fetal NBM ( hf NBM) as immature cholinergic neurons expressing the machinery to synthetize and release acetylcholine. Here we studied in detail electrophysiological features and cholinergic effects in this cell culture by patch‐clamp recordings. Our data demonstrate that atropine‐blocked muscarinic receptor activation by acetylcholine or carbachol enhanced IK and reduced INa currents by stimulating Gi ‐coupled M2 or phospholipase C‐coupled M3 receptors, respectively. Inhibition of acetylcholine esterase activity by neostigmine unveiled a spontaneous acetylcholine release from hf NBM neuroblasts that might account for an autocrine/paracrine signaling during human brain development. Present data provide the first description of cholinergic effects in human NBM neurons and point to a role of acetylcholine as an autocrine/paracrine modulator of voltage‐dependent channels. Our research could be of relevance in understanding the mechanisms of cholinergic system development and functions in the human brain, either in health or disease. Abstract : We demonstrate here that cells isolated from the nucleus basalis of Meynert (NBM) of 12‐week‐old human fetuses are cholinergic neuroblasts able to retain immature features for at least three months in mitogen‐free culture medium and to synthesize and release acetylcholine (ACh), as well as to sense extracellular ACh. Activation of M2 muscarinic receptors enhance tetraethylammonium (TEA)‐sensitive K + currents by Gi/o‐coupling, whereas M3 receptors inhibit tetrodotoxin (TTX)‐sensitive Na + channels by pholspholipase C (PLC) activation. In the presence of atropine, ACh activates nicotinic receptor‐dependent currents.